Religious tourism and emotional experiences: An emotional cartography of Jerusalem - Ion Gil Fuentetaja; Marina Abad-Galzacorta (International Journal of Religious Tourism and Pilgrimage)
An increasingly important segment of cultural tourism relates to ‘religious travel’, tourism motivated by spiritual reasons or associated with religious heritage sites. Thus, travel agencies are offering extensive journey packages to ancient places of worship, sacred destinations and pilgrimage sites. In this sense, according to data offered by the Ministry of Tourism of Israel, around one fifth of tourists to the country expressed religious tourism or pilgrimage as the main purpose of their visit. Additionally, tourism is greatly founded on the consumption of experiences. Understanding the ways in which tourists experience the places is, therefore, fundamental to the study of the consumption of tourism and, in particular, of religious tourism and pilgrimage. Consequently, measuring the emotional situation of these tourists is crucial for the fulfilment of their expectations and, logically, for the degree of overall satisfaction of the experience itself. Accordingly, this paper presents the preliminary results of the experimental implementation of an emotional measurement system in the context of a spiritual journey to Holy the Land during Easter 2015. This is a first trial out of a laboratory and, therefore, one controlled volunteer, whose primary motivasults of the experimental implementation of an emotional measurement system in the context of a spiritual journey to Holy the Land during Easter 2015. This is a first trial out of a laboratory and, therefore, one controlled volunteer, whose primary motivation was pilgrimage, was selected to test the suitability of the method for measuring the emotional situation of the individual while in the aforementioned religious travel. The paper proposes an integrated framework of verbal and non-verbal measurement approaches and, together with spatial and temporal information, generates an emotional cartography of the Holy Land based on this journey. Initial findings suggest that emotional situation is influenced not only by space factors, but also by temporal and religious contextual factors surrounding the visitor. Even though results of the trial respond to a single case that should be expanded to contrast the obtained conclusions, it can be affirmed that there are significant implications for researchers and their methodological practices, particularly regarding the spiritual aspects of emotional engagement in religious tourism.